AN ANALYSIS OF STUDENTS' DIFFICULTIES IN LEARNING ENGLISH AT ISLAMIC BOARDING SCHOOL AL-MURABBI NIPAH KUNING - Mahrus, Haris (FKIP UM Pontianak, 2025)
English learning in Islamic boarding schools plays a vital role in preparing students for global communication. However, limited studies have explored this context, especially in rural areas such as Kubu Raya, West Kalimantan. This research addresses that gap by examining the difficulties faced by students in learning English informally at Al-Murabbi Islamic Boarding School. The study aims to identify major challenges influencing students’ English learning within informal environments. Employing a case study with qualitative approach, data were gathered from ten students and two English tutors through observation, interviews, and documentation. The findings revealed three key difficulties including linguistic, psychological, and environmental Factors. Linguistic difficulties involved limited vocabulary, grammatical weaknesses, and pronunciation errors. Psychological barriers included fear of making mistakes, anxiety, and low self-confidence, which reduced students’ willingness to communicate. Environmental factors, such as peers’ use of local languages and lack of English exposure, further limited practice opportunities. These findings indicate that mastering English requires more than language skills; students also need emotional support and a positive environment. Therefore, pesantren should encourage more English practice through peer interaction, provide English-speaking areas, and build students’ confidence to improve their informal communication.